Promoting sustainable dietary patterns through fast food restaurants’ Corporate Social Responsibility (CSR) - Tahir, Nor Suziwana; Muhammad Zamri, Nor Ezatie Mukminah; Abd Hamid, Siti Nur Fathanah; Ahmad, Yarina; Bustami, Mohammad Reevany (2023)
Nowadays, the global obesity prevalence demonstrates an alarming increase, and this urges the World Health Organization (WHO) to introduce “globesity” term. The increased obesity risk worldwide is relevant to Goal No. 3 of Sustainable Development Goals (SDGs). Overweight and obesity are leading risk factors for cardiovascular diseases and type 2 diabetes and major contributors to premature death. Addressing overweight and obesity must begin from the young generation to reduce the risk of obesity in adulthood. In Malaysia, overeating and imbalanced meals are parts of the bad eating habits of obese people. Since the 1990s, the fast-food restaurants have experienced heavy growth and past literatures postulate that the prevalence of fast food consumption is high among the young generation. Due to changing lifestyles and high consumer demand for healthier food, many fast-food restaurants have been modifying their menus by introducing healthier food options. The fast-food restaurants also demonstrate their commitment by implementing various Corporate Social Responsibility (CSR) policies that aimed at promoting the adoption of healthy diet and these initiatives aligned with the idea of Stakeholder Theory. Hence, this study aims to examine the influence of Carroll’s CSR dimensions which are economic, legal, ethical, and philanthrophic responsibilities undertaken by the fast-food restaurants towards promoting sustainable dietary patterns among the young generation. 400 young generation aged between 18 and 30 years old answered the survey. The questionnaires comprised of six sections and the respondents were chosen by using stratified random sampling technique. All items were adopted and adapted from past studies. Reliability and validity analysis were performed, and the data were further analysed by using Decsriptive Analysis and Multiple Regression Analysis to answer the research questions. This study concludes that three CSR dimensions (economic, legal and ethical) embedded in the fast-food restaurants’ CSR activities positively influence the sustainable dietary patterns of the young generation. The findings of this study assist the fast-food industries to establish a sound CSR strategy and provide supporting data to policy makers and relevant government agencies to promote healthy eating habits among the young generation.